Apocalyptic Collapse and the Absurd in Vonnegut’s Cat’s Cradle - Ruth Fialho (Caliban: French Journal of English Studies)
This article analyzes the way Kurt Vonnegut develops an aesthetics of the grotesque to examine the irresistible attraction humankind feels for self-destruction. In Cat’s Cradle, he evokes science, religion and our desire for Utopia to describe our unstoppable march toward the Apocalypse. Each of the aforementioned organizing systems is exposed as one same expression of our desire for control, which can only lead to radical failure. For Vonnegut, there is only one road to salvation: acknowledging the absurd as the organizing principle of our lives.